The C-Type Lectin Receptor SIGNR3 Binds to Fungi Present in Commensal Microbiota and Influences Immune Regulation in Experimental Colitis - Eriksson, Magdalena; Johannssen, Timo; von Smolinski, Dorthe; Gruber, Achim D.; Seeberger, Peter H.; Lepenies, Bernd (Frontiers in Immunology, 2013)
Inflammatory bowel disease is a condition of acute and chronic inflammation of the gut. An important factor contributing to pathogenesis is a dysregulated mucosal immunity against commensal bacteria and fungi. Host pattern recognition receptors sense commensals in the gut and are involved in maintaining the balance between controlled responses to pathogens and overwhelming innate immune activation. C-type lectin receptors (CLRs) are pattern recognition receptors recognizing glycan structures on pathogens and self-antigens. Here we examined the role of the murine CLR SIGNR3 in the recognition of commensals and its involvement in intestinal immunity. SIGNR3 is the closest murine homologue of the human DC-SIGN receptor recognizing similar carbohydrate ligands such as terminal fucose or high-mannose glycans. We discovered that SIGNR3 recognizes fungi present in the commensal microbiota. To analyze if this interaction impacts the intestinal immunity against microbiota, the dextran sulfate sodium (DSS)-induced colitis model was employed. SIGNR3-/- mice exhibited an increased weight loss associated with more severe colitis symptoms compared to wild-type control mice. The increased inflammation in SIGNR3-/- mice was accompanied by a higher level of TNF-α in colon. Our findings demonstrate for the first time that SIGNR3 recognizes intestinal fungi and has an immune regulatory role in colitis.